La nueva sinología española - Herrera Feligreras, Andrés (Huarte de San Juan. Geografía e Historia, 2007)
Despite de fact that Castilla was a pioneer regarding Chinese approach policy with Europe, over XVI century, the arising of the Asian gigant in the context of the new global order has had to come for making it possible to rediscover the “Kingdom of the Centre” in Spain. At first decade of XXI century’s door, we witness the set up of a new Spanish sinology in a world situation where there exist the conditions to acquire a better knowledge about Chinese culture than the knowledge we had until last decades of XX century in our country.
Keywords: China; Spain; spanish scientific production; sinology